ETUDE DES FACTEURS INFLUENÇANT LA DUREE DE GESTATION ET LA VARIATION DES PARAMETRES BIOCHIMIQUES SELON LE STADE DE REPRODUCTION CHEZ LA JUMENT ARABE. - MELIANI Samia (My University, 2013)
1262 thoroughbred mares belonging to the Arab National Stud Chaouchaoua Wilaya of Tiaret (Algeria) were monitored during the period that spanned from 1985 to 2010. During the first part of the study, with the aim to determine the length average of gestation in the thoroughbred Arabian mare, was estimated at 332.95 ± 8.57 days, while the shortest average encountered, with a viable product, was 327.22 ± 8.11 days in 2004, and the longest length average was encountered in 1999 with 338.48 ± 7.28 days. This wide variability in the gestation period giving a viable foal indicates that the gestation duration in the mare is very sensitive to genetic and environmental factors as, year and month of breeding, age of mother and sex of the foal. The study of follicular growth of our mares showed that the mean diameter of dominant follicles was 31.50 ± 6.36 mm. The remaining mares had only small follicles on the ovaries. One day before ovulation, the average follicular diameter was 43.16 ± 4.91 mm. The average diameter of follicular development was very high in four days before ovulation, with 3.53 mm / day. The second part of the study has tracked the evolution of the concentration of some constituents of blood plasma such as calcium, inorganic phosphorus, magnesium, sodium, potassium, glucose and triglycerides in the different reproduction phases in mares. Infertile mares had a serum calcium with relatively high 3.78 ± 0.51 mmol / L compared to that of postpartum mares with 2.74 ± 0.09 mmol / L probably less use of calcium by the body in the absence of pregnancy or milk production. Similarly, serum inorganic phosphorus with the fillies was significantly higher than among other groups of mares (P <0.05) with 1.32 ± 0.25 mmol / L. While lower rates, were observed in postpartum mares with 0.81 ± 0.08 mmol / L and those in late pregnancy with 0.91 ± 0.11mmol /L. Serum concentrations recorded minerals, glucose and triglycerides vary according to different phases of the reproductive cycle of mares.
Keywords: Thauroghtbred Arabian mares, Preganancy duration, Follicular diameters, Blood parameters.